A brief review on plasma for synthesis and processing of electrode materials - Ouyang, Bo (2019)
Plasma, as an active, ionized, and electrically neutral gas, consists of electrons, ions, molecules, radicals, photons, and other excited species. Owing to its high activity, plasma can induce rapid and efficient reactions under relatively mild conditions. Hence, plasma has emerged as a powerful tool for material processing in both industrial and laboratory scale. This review provides a timely summary of different plasma techniques and their application in electrode materials. We first provide a brief introduction to the nature of plasma and types of plasma technologies. Then we summarize the recent advance in material synthesis and processing (deposition, conversion reaction, and surface modification) via plasma-assisted techniques with different feedstocks (C, H, N, O, Ar, S, P, etc.). Our focus is to put on electrode materials for energy conversion and storage devices, including batteries, supercapacitors, photocatalyst, and electrocatalysts. The advantages of plasma approaches over conventional technologies are discussed with examples.